Case report: Functional characterization of a novel CHD7 intronic variant in patients with CHARGE syndrome - Rossi, Cesare; Ramadan, Sherin; Evangelisti, Cecilia; Ferrari, Simona; Accadia, Maria; Toydemir, Reha M.; Panza, Emanuele (Frontiers in Genetics, 2023)
Background: Because CHARGE syndrome is characterized by high clinical variability, molecular confirmation of the clinical diagnosis is of pivotal importance. Most patients have a pathogenic variant in the CHD7 gene; however, variants are distributed throughout the gene and most cases are due to de novo mutations. Often, assessing the pathogenetic effect of a variant can be challenging, requiring the design of a unique assay for each specific case. Method: Here we describe a new CHD7 intronic variant, c.5607+17A>G, identified in two unrelated patients. In order to characterize the molecular effect of the variant, minigenes were constructed using exon trapping vectors. Results: The experimental approach pinpoints the pathogenetic effect of the variant on CHD7 gene splicing, subsequently confirmed using cDNA synthetized from RNA extracted from patient lymphocytes. Our results were further corroborated by the introduction of other substitutions at the same nucleotide position, showing that c.5607+17A>G specifically alters splicing possibly due to the generation of a recognition motif for the recruitment of a splicing effector. Conclusion: Here we identify a novel pathogenetic variant affecting splicing, and we provide a detailed molecular characterization and possible functional explanation.